Kinerja Modulasi BPSK Modem Software Defined Radio pada DSK TMS320C6713 - Sapriesty Nainy Sari (Fakultas Teknik, Universitas Brawijaya, 2016)
Abstract— Software Defined Radio (SDR) is a signal processing technology that optimizes the use of PC as a device supporting. With the application of SDR in wireless communication system so it will provide possibility and flexibility on manipulating DSP without the need of hardware changes. SDR modems are designed to take advantage of Digital Signal Processor Starter Kit (DSK) TMS320C6713 for baseband signal processing. In the implementation phase, the DSK is programmed directly using Matlab Simulink integration to build a system of modulation and demodulation Binary Phase Shift Keying (BPSK). Sampling frequency 8000 kHz is used with a variety of bit rate of 1 kbps and 2 kbps.